High BMI leads to increased breast cancer risk in postmenopausal women - Tantoso, Tifanny; Sitorus, Mega Sari; Feriyawati, Lita; Wahyuni, Dian Dwi (Talenta Publisher, 2021)
Obesity is a worldwide problem that has been steadily increasing even in developing countries. Obesity has been linked to various types of cancer, one of which is breast cancer. Breast cancer has been classified into various types based on gene and hormone receptor expressions, which offered new insights to therapies and prognoses. We conducted a case-control study using 42 breast cancer patients and 43 healthy women, all of which are older than 55 years of age and have experienced menopause, and for case subjects, additional immunohistochemistry profiles have been provided. Data were collected by interviews and medical records. For data analysis, we used Pearson’s Chi-Square test and Fisher’s Exact test. Results showed that high BMI is significantly associated with breast cancer, and risk is elevated (p < 0.05, OR = 1.263, 95% CI = 1.007-1.583). No significant association with molecular subtypes was observed.